玉米醇溶蛋白-乙基纤维素复合薄膜的 制备工艺优化及其表征和应用Optimization of preparation process of zein-ethyl cellulose composite film and its characteristics and application - 张书凝，周家劲，许盼盼，闫枫丹，毕艳兰，彭丹，李军 ZHANG Shuning, ZHOU Jiajin, XU Panpan, YAN Fengdan, BI Yanlan, PENG Dan, LI Jun (Zhongguo youzhi)
为制备一种可用于高含油食品的涂膜保鲜包装材料，以玉米醇溶蛋白和乙基纤维素为原料制备复合薄膜，通过单因素实验研究玉米醇溶蛋白与乙基纤维素质量比、乙醇体积分数、增塑剂种类及添加量和固化温度对复合薄膜机械性能和阻隔水蒸气、氧气性能的影响，对复合薄膜的制备工艺进行优化，对复合薄膜的断面形貌、化学结构、表面水接触角进行表征，并探究复合薄膜的应用效果。结果表明：复合薄膜的最佳制备工艺条件为玉米醇溶蛋白与乙基纤维素质量比3∶ 7、乙醇体积分数87%、增塑剂为油酸、油酸添加量0.2 g/g（以总固体质量计）、固化温度60 ℃，在此条件下复合薄膜的拉伸强度为23.29 MPa，断裂伸长率为12.03%，水蒸气透过率为5.99 g·mm/(m2·d·kPa)，此薄膜密封的桐油过氧化值增长率为299.40%；复合薄膜相容性良好，2种成膜基材发生物理复合。复合薄膜水接触角较原料薄膜升高，为82.0°，表明其表面疏水性有所提升；60 ℃加速氧化储藏实验结果显示，相比初始过氧化值，未包膜花生碎中油脂的过氧化值上升1.53倍，包膜花生碎中油脂的过氧化值上升1.32倍，证明复合薄膜包被可减缓花生碎氧化速率。综上，制得的可食用薄膜包衣机械性能良好，具有隔水、隔氧能力，可提升高含油食品的抗氧化能力，延长其货架期。 To prepare a coating preservation packaging material applied in foods with high oil content, zein and ethyl cellulose (EC) were used as the raw materials to prepare composite film, the effects of mass ratio of zein to EC, ethanol volume fraction, type and dosage of plasticizers, and curing temperature on the mechanical properties, water vapor and oxygen barrier property of the composite film were investigated by single factor experiment to optimize the preparation process of the composite film. Cross-sectional morphology, chemical structure, and surface water contact angle of the composite film were analyzed. The applied effects of the composite film were also investigated. The results showed that the optimal preparation conditions were as follows: mass ratio of zein to EC 3∶ 7, ethanol volume fraction 87%, oleic acid as plasticizer with the dosage of 0.2 g/g (based on the total solid mass), and curing temperature 60 ℃. Under these conditions, the tensile strength of the composite film was 23.29 MPa, elongation at break was 12.03%, water vapor permeability was 5.99 g·mm/(m2·d·kPa), and the growth rate of peroxide value of tung oil sealed with the prepared film was 29940%. The composite film was well-compatible, the two film-forming substrates were physically compounded. The water contact angle of the composite film was 82.0°, which was higher than that of the zein or EC film, indicating that its surface hydrophobicity was improved. Accelerative oxidation experiment at 60 ℃ showed that compared with the initial peroxide value, the peroxide value of uncoated peanut chunks increased by 1.53 times, while the peroxide value of coated peanut chunks increased by 1.32 times, demonstrating that film coating can slow down the oxidation rate of peanut chunks. In summary, an edible film with excellent mechanical and water and oxygen barrier properties for coating preservation is successfully prepared, which can improve the oxidative stability of foods with high oil content and extend their shelf life.